1981
DOI: 10.1002/jcp.1041090218
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipids: Receptors for fibronectin?

Abstract: We have examined the hypothesis that glycolipids might serve as receptors for the cell surface glycoprotein fibronectin using three different biological assay systems. We find that purified solubilized gangliosides inhibit fibronectin-mediated hemagglutination, cell spreading, and restoration of a normal morphologic phenotype to transformed cells. The inhibition is dose-dependent and competitive; hemagglutination by 2 micrograms/ml fibronectin is half-maximally inhibited by less than 1 microM gangliosides. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 31 publications
6
64
0
Order By: Relevance
“…We also demonstrated that pretreatmerit of human melanoma cells with either anti-GD2 or anti-GD3 Mabs inhibited their ability to attach to a number of extracellular matrix proteins (10). These data are in support of the studies that implicate gangliosides in cell-substratum interactions (18,29,49). The conclusion reached in these reports were based upon the exogenous addition of gangliosides to cultured cells under the assumption that the exogenously added gangliosides could embed appropriately in the plasma membrane of the cells being examined.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We also demonstrated that pretreatmerit of human melanoma cells with either anti-GD2 or anti-GD3 Mabs inhibited their ability to attach to a number of extracellular matrix proteins (10). These data are in support of the studies that implicate gangliosides in cell-substratum interactions (18,29,49). The conclusion reached in these reports were based upon the exogenous addition of gangliosides to cultured cells under the assumption that the exogenously added gangliosides could embed appropriately in the plasma membrane of the cells being examined.…”
Section: Discussionsupporting
confidence: 80%
“…A number of reports have indicated that the exogenous addition of polysialogangliosides to fibronectin-attached cells caused them to round up and detach from the substrate (18,29,49). These studies led to the conclusion that gangliosides may act as specific fibronectin receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-surface gangliosides have been regarded as receptors for FN (Yamada et al, 1981;Perkins et al, 1982;Matyas et al, 1986). In this study, exogenous GM1 was potentially able to inhibit the interaction between FN and cell-surface GM1 by taking over the GM1-binding sites of substrate-coating FN or plasma FN in FCS.…”
Section: % Fcsmentioning
confidence: 66%
“…(Yamada et al, 1981;Perkins et al, 1982;Matyas et al, 1986) as obviously shown in the morphological images (Figure 4). By calculating the percentage of spread cells, we found that GM1 significantly inhibited the spreading of HUVECs on FN-coated coverslips in medium supplemented with or without 0.5% FCS (but not 10% FCS) only at 0.5 h compared with the GM1-free control ( Figure 5A).…”
Section: Inhibitory Effects Of Exogenous Ganglioside Gm1 On Cell Sprementioning
confidence: 87%